Acute toxicity of three antifungal chemicals on silverside Odontesthes bonariensis (Valenciennes 1835) eggs - Pacheco Marino, Suani Giovanna (2010)
The effects of sodium chloride (NaCl) and formalin (F) on some toxicological parameters and the hatching rate of Odontesthes bonariensis eggs were examined under laboratory conditions, and the determined values were compared with those obtained for Malachite Green (MG), which was used as a reference toxic. The 96 hours nominal LC50 were 1.51 mg L-1, 652.14 μl L-1 and 34.82 g L-1 for MG, F and NaCl, respectively. The No-Observed-Effect Concentration (NOEC) and the No-Effect Concentrations (NEC) were 1.5 mg L-1 and 0.507 mg L-1 (MG), 400 μl L-1 and 530 μl L-1 (F) and 30.0 g L-1 and 28.68 g L-1 (NaCl), respectively. Hatching rates of 60% or higher were determined for eggs after 168 hours incubation in the assayed solutions at concentrations of 0.75 mg L-1 (MG), 300 μ L-1 (F) and 20 g L-1 (NaCl); at higher concentrations the hatching rates were severely affected.